Analisa Dan Perancangan Website Tes Psikologi (Study Kasus Fakultas Kedokteran Dan Ilmu Kesehatan Universitas Negeri Jambi) - Dodi Setiawan; Rusdianto Roestam (Jurnal Manajemen Sistem Informasi, 2017)
Unja ( Universitas Negeri Jambi ) is one of the universities that there dijambi which has a psychologydepartment is one of the educational institutions that have applied information technology both learningmaterials in the field of information technology to the process of academic information systems. AtUniversity has a department of psychology and for the acceptance of new students majoring inpsychology test conducted at this time there are still some shortcomings in terms of slow overallassessment and obtain reports test results that take a lot of time. To overcome all these problems, theresearchers conducted an analysis system Psychological test are ongoing. The object of research focusingon the system Psychological test that have been run and the scope and phases of the systems developmentlife cycle is the purpose of this study is limited to the analysis and design to the prototype. In designingthe system of psychological test online using web-based programming by using PHP and MySQL. Thepurpose of this research is to study and analyze the existing problems in the system of psychological testthat are running test admissions psychology at University as well as designing web-based system ofpsychological test new. Analysis and design of web-based system of psychological test developed will beexpected to overcome the existing problems to the admission process of psychological test can bemanaged online.